Analisis Perilaku Konsumen Dalam Pembelian Produk Seafood Fried Rice Pada Resto Angel’s Wing Kota Bengkulu - Monica Anwar; Ririn Afriani (Jaanur Elbarik Indonesia, 2026)
Bengkulu City has great potential in the agribusiness sector, especially in the development of culinary industries based on abundant marine resources. One of them is through Seafood Fried Rice dishes that combine fried rice with fresh seafood ingredients such as shrimp, squid, and fish. The purpose of this research was to analyze the stages of the purchasing decision process for Seafood Fried Rice products at Angel's Wing Bengkulu City and analyze the factors that influence consumer behavior in purchasing Seafood Fried Rice products at Angel's Wing Bengkulu City. In this research, an analysis was conducted on the factors that influence consumer purchasing decisions, namely price, lifestyle, income, culinary image, and peer support. The method used is a quantitative approach by distributing questionnaires to 100 respondents who visited the restaurant. The collected data were then analyzed using descriptive analysis and multiple linear regression analysis. The results of the research indicate that the stages of the purchasing decision process go through five main stages: need recognition, information search, alternative evaluation, purchase decision, and post-purchase behavior. Factors influencing the decision to purchase Seafood Fried Rice at Angel's Wing in Bengkulu City are income (X3) and peer support (X5), while price (X1), lifestyle (X2), and culinary image (X4) do not influence the decision to purchase Seafood Fried Rice at Angel's Wing in Bengkulu City.